Gearing up education towards Industry 4.0 - Umachandran, Krishnan; Jurcic, Igor; Ferdinand-James, Debra; Said, Mohamed Mohamed Tolba; Abd Rashid, Adnan (Council for Innovative Research (CIRWORLD), 2018)
Industry has changed creatively with manufacturing systems and technological applications supplementing in the work preparation, reporting variants, methods and resources for effective production management by constant improvements and usage has matured it way to Industry 4.0. Industry has undergone various revolutions up to now, and through cyber-physical systems would communicate, collaborate in real time of the process and product value stream. Technology upgrades will bring optimization in various resource utilization and focus on satisfying customers even over their ever increasingly demand. The gadgetry conveniences would bring the wearable’s and embedded handle large databases for dynamic mining and interpretations obsoleting the necessity of strain in carrying laptops or pads. Innovation would be successful as it facilitates quick product developed self-customized for use at the shortest development time. Studentcentered learning, learning consequences will have lifelong erudition where educational institutions will develop robust integrated systems and infrastructure to facilitate learning by doing rather than by the conventional learning. New age of Industry 4.0 will bring in a considerable change in physical world as in the virtual facilitation enabled by digital connect shrinking the distances, removing differences, and conducting real time transfer knowledge and material transfer globally. Being technologically prepared is the need of the time then to wait for the opportunity to push the educational system to change, where the time loss would handicap the economy and younger generations to be forced to compete even with perceived incapable and smaller frugalities.